'Preparation and Transition into Adult Life—Guide for Professionals': An Educational Tool from the SOS Children's Villages. Issue 2 (September 2022) - Lobo, Joana; Urbano, Cláudia; de Carvalho, Maria João Leote
SOS Children's Villages work to protect and improve the lives of children and young people placed in alternative care system. The goal is to break the cycle of family and social disadvantage within this framework, it is essential to provide tools to professionals to support young people path towards autonomy and social integration as active citizens in civil society. This article aims to present and discuss the preparation and transition into adult life—A guide for professionals recently implemented in SOS Children's Villages, Portugal, within the context of Project PORTA. Educating for autonomy arises as the main concern for the organization, individually and collectively, since it is responsible for the care and support of development needs of children and young people in its programmes. With this aim, this guide helps professionals and young people to promote better practices for developing autonomy skills and preparing transition to adult life, through the explanation of resources and structured intervention individual plans. Thereby, knowledge and practices are shared, expecting to be useful for others as well. A special focus is dedicated to the reinforcement of specific skills, protective factors and social areas, aiming the preparation for autonomy people in close collaboration with all the intervenient and, in particular, with the participation of young people.